Connected Mobilities in the Early Modern World The Practice and Experience of Movement - Nelles, Paul (Hrsg.); Salzberg, Rosa (Hrsg.) (London Taylor & Francis Ltd; Routledge, 2025)
Movement and Mobility in the Early Modern World: An Introduction (Paul Nelles and Rosa Salzberg), MOVING BODIES, Chapter One Linguistic Encounter: Fynes Moryson and the Uses of Language (John Gallagher), Chapter Two Wading Through the Mire. Mobility on the Grand Tour (1585-1750) (Gerrit Verhoeven), Chapter Three Travelling for Health: Medicine and Rural Mobility in Early Modern Spain (Carolin Schmitz), CROSSING BORDERS, Chapter Four Mobility and Danger on the Borders of the Papal States (16th-17th Centuries) (Irene Fosi), Chapter Five News on the Road: the Mobility of Handwritten Newsletters in Early Modern Europe (Paola Molino), Chapter Six Quarantine, Mobility, and Trade: Commercial Lazzarettos in the Early Modern Adriatic (Darka Bili.), GLOBAL NETWORKS, Chapter Seven Devotion in Transit. Agnus Dei, Jesuit Missionaries, and Global Salvation in the Sixteenth Century (Paul Nelles), Chapter Eight Getting to the Holy Land: Franciscan Journeys and Mediterranean Mobility (Felicita Tramontana), Chapter Nine From Mount Lebanon to the Little Mount in Madras: Mobility and Catholic-Armenian Alms-Collecting Networks During the Eighteenth Century (Sebouh Aslanian), Index.
E-Book / Zugriff nur im Lesesaal